Можливості визначення глікованого фібриногену плазми крові як критерію компенсації цукрового діабету у вагітних - Каліман, В. П. (Clinical Endocrinology and Endocrine Surgery, 2010)
In the article discussed a possibility of diagnostics of uncompensated carbohydrate states at pregnant women with diabetes mellitus typef Ι and ΙΙ by determination of glycated fibrinogen content in blood plasma after formation of stable ketamine compound.